PENANAMAN NILAI-NILAI PENDIDIKAN KARAKTER MELALUI EKSTRAKULIKULER PENCAK SILAT DI SMAN 1 KOTA SUKABUMI: PENANAMAN NILAI-NILAI PENDIDIKAN KARAKTER MELALUI EKSTRAKULIKULER PENCAK SILAT DI SMAN 1 KOTA SUKABUMI - Risandri, Irgi; Carsiwan; Rahmat, Alit (Jurnal Pedagogik Olahraga, 2025)
This study aims to describe the instillation of character education values through extracurricular activities of pencak silat sports at SMAN 1 Sukabumi City. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The research subjects consisted of 25 students participating in the pencak silat extracurricular and the activity instructors. The results of the study indicate that in the implementation of the pencak silat extracurricular, the character values instilled include religious, honest, disciplined, hard work, creative, caring for the environment, and love of peace. The recapitulation of the observation results shows that the number of "yes" answers was 1,222 or 81%, while the number of "no" answers was 278 or 19%, which indicates that the process of instilling character values is in the good category (76%–100%). Thus, the pencak silat extracurricular activities contribute positively in shaping the character of students at SMAN 1 Sukabumi City.